Culture medium and varietal selection for establishment of callus culture of Artemisia annua - Chin, Chee Keong (Universiti Pendidikan Sultan Idris, 2018)
Culture medium and varietal selection for establishment of callus culture of Artemisia annua by Chin, Chee Keong